Nghiên cứu chế tạo, khảo sát cấu trúc và tính chất vật liệu compozit etylen vinyl axetat copolyme/nanoclay hữu cơ - Kim, Nguyễn Thạc; Hoàng, Thái; Hà, Khương Việt; Thẩm, Đỗ Quang (Vietnam Journal of Chemistry, 2014)
Ethylene-vinyl acetate copolymer (EVA)/organic montmorillonite (O-MMT) composites were prepared via direct melt mixing EVA containing vinyl acetate (VA) of 9% with O-MMT in an intermixed Haake at 160oC. The relative melt viscosity of EVA and EVA/O-MMT composites were evaluated according to changing of torque of the materials during melt mixing process. Their structures were investigated with X-ray diffraction (XRD) and scanning electron microscopy (SEM). The electrical parameters of composites were measured by the dielectric loss measuring set. The results showed that the torques of EVA/O-MMT composites increase with rising O-MMT content. The XRD patterns indicated that EVA chains could be intercalated into the interlayer gallery of O-MMT and interacted with O-MMT, leading to expansion of the interlayer space, but not yet destroyed their layered structures. The SEM photographs proved the existence of both nanostructure and microstructure in the EVA/O-MMT composites.